"I Had Not Seen Star Wars" and Other Motives for Divorce in Denmark. Issue 1 (2nd January 2020) - Strizzi, Jenna Marie; Sander, Søren; Ciprić, Ana; Hald, Gert Martin
Abstract: A total of 2, 371 Danish residents participating in the Cooperation After Divorce randomized controlled trial study indicated the motives for their divorce. The most frequently given motives were lack of love/intimacy, communication problems, lack of sympathy/respect/trust, and growing apart. The least reported motives were violence, addiction, accident or illness, and personality. The results support global trends regarding an increased importance of emotional and psychological aspects of relationships. A factor analysis seeking to identify clusters in the motives did not yield statistically or theoretically strong results. This may indicate that experiences with and motives for divorce are heterogeneous and multifactorial.